Identifying entity and attributes of God: an Islamic perspective = Mengenal pasti entiti dan sifat-sifat Allah: satu perspektif Islam - Khan, Israr Ahmad (IIUM Press, 2016)
Concept of Supreme Being is as old as the human history itself. But the idea of entity and attributes of that Being varies from culture to culture and religion to religion. Islam gives very vivid image of God, namely Allah in terms of His entity, attributes, and nature of relationships with the creature, including man. The Arabic word Allah denotes in English “The God”. He is Only One without any partner. He is totally unseen. He is the Creator, Sustainer, Provider, Controller of the entire universe. All that is in the earth and heavens belong to Him. Nothing is unto like Him. His power is infinite. He is as close to man as his jugular vein. He is the Most-Merciful, the Most-Beneficent. He is eternal with no beginning and end. He interacts with man and communicates to him every moment. He is Just and loves those who subscribe to justice. He has forbidden injustice for Himself as well as for man. He is Generous and commands man to interact with others generously. In order to be close to Him man has to be as kind to others as to his own self. The qualities Allah wants to see in man include sincerity, honesty, truthfulness, trustworthiness, justice, generosity, altruism, tolerance, forbearance, and fortitude. This paper deals with all these dimensions of “The God” from Islamic perspective as available in the Qur’an and the Prophetic traditions.